A Hardware Model to Measure Motion Estimation with Bit Plane Matching Algorithm - Shaik Asif Hussain; Chandrashekar Ramaiah; S. Javeed Hussain (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The multistep approach involving combination of techniques is referred as motion estimation. The proposed approach is an adaptive control system to measure the motion from starting point to limit of search. The motion patterns are used to analyze and avoid stationary regions of image. The algorithm proposed is robust efficient and the calculations justify its advantages. The motivation of the work is to maximize the encoding speed and visual quality with the help of motion vector algorithm. In this work a hardware model is developed in which a frame of pictures are captured and sent via serial port to the system. MATLAB simulation tool is used to detect the motion among the picture frame. Once any motion is detected that signal is sent to the hardware which will give the appropriate sign accordingly. This system is developed on two platforms (hardware as well software) to estimate and measure the motion vectors.